PEMANFAATAN CITRA SATELIT UNTUK MENGANALISIS DAMPAK LIKUIFAKSI TERHADAP PERUBAHAN PENGGUNAAN LAHAN DAN TUTUPAN VEGETASI DI DESA PETOBO, KOTA PALU, TAHUN 2018 - Nurwahyudin, Muhamad (JURNAL GEOGRAFI, 2024)
This study aims to analyze the impact of liquefaction, especially in Petobo village, Palu City, Central Sulawesi in 2018. This research was studied through several approaches and analytical methods in remote sensing. In this case, it identifies various impact parameters ranging from topographic and land-use change patterns based on OBIA (Object Based Image Analysis) analysis, and Change Detection. On the other hand, analysis of greenness, vegetation density and surface temperature using NDVI, MSARVI and LST (Land Surface Temperature) methods. Spatial and temporal analysis was conducted to understand the evolution of liquefaction phenomena and their impact in the Petobo Village area. The results of this research show the impact of liquefaction disasters in terms of increasing temperature, vegetation, and land use changes with various methods of approach. As a result, 156.0182 hectares is the area affected by liquefaction. The temperature before the earthquake had a temperature of 26°C increased by 2°C to 28°C. In liquefaction areas, vegetation density decreased by 100% due to likquifaction or almost 78 hectares experienced a significant decrease in vegetation density. As much as 6.8% of vegetation land, 1.6% of built-up land, and 10.7% of agricultural land increased. Meanwhile, vacant land was reduced by 19.1% .Keywords : Liquefaction, Impact, Remote Sensing